2003
DOI: 10.1309/cepk-542w-3885-2lp8
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Papillary-Mucinous Neoplasm of the Pancreas: The Findings and Limitations of Cytologic Samples Obtained by Endoscopic Ultrasound-Guided Fine-Needle Aspiration

Abstract: All clinically and ultrasonographically suspected examples of intraductal papillary-mucinous neoplasm (IPMN) aspirated during a 17-month period were reviewed and analyzed for follow-up. We identified 18 cases of suspected IPMN in patients 52 to 87 years old. All patients had dilated pancreatic ducts, with 3 showing sonographically apparent intraductal papillary lesions; 5 had adjacent cystic or solid pancreatic masses. Cytologic preparations showed thick, glistening, viscid, abnormal mucus in all cases. Aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 45 publications
0
65
0
2
Order By: Relevance
“…Additionally, cyst fluid may be evaluated for microRNAs or for mucins. When integrated with clinical findings, such molecular approaches have the potential of fundamentally changing the way cystic neoplasms of the pancreas are managed [120][121][122][123][124].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cyst fluid may be evaluated for microRNAs or for mucins. When integrated with clinical findings, such molecular approaches have the potential of fundamentally changing the way cystic neoplasms of the pancreas are managed [120][121][122][123][124].…”
Section: Discussionmentioning
confidence: 99%
“…It has proven to be a valuable tool in the preoperative diagnosis and management of patients with pancreatic lesions. [1][2][3][4][5][6] Whereas most aspirations yield diagnostic material, the differential diagnosis of the reactive/reparative and neoplastic processes as well as their precise classification in the pancreatic EUS-FNAs specimens can be challenging. This can be explained by the considerable overlap in the cytomorphologic features of these processes in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Ductal adenocarcinoma is the most common malignancy of the pancreas. 7 Recently, it has been shown that the malignant transformation of pancreatic ductal epithelium changes the epithelial expression of apomucins.…”
mentioning
confidence: 99%
“…What can explain such high specificity and low sensitivity for cytology is that the presence of sticky fluid on aspiration or mucin in cytology is highly diagnostic for mucinous cysts. However, aspirate can be acellular or with minimal cellularity in up to 72% of aspirated cysts [49,50]. FNA is not useful in SCA with diagnostic accuracy of only 17% [51].…”
Section: Cytological Evaluationmentioning
confidence: 99%